Salivia moorcroftiana a New Host for Sclerotium rolfsii Sacc. in India−its Management with Botanicals and Fungicides - Chandel, Sunita; Gupta, A. K. (International Journal of Bio-resource and Stress Management, 2016)
Salvia is the largest genus of plants in the mint family and is one of the important medicinal plants. Salvia spp. are valued for essential oil, flavor compounds and their possible uses have been registered as an antisweating agent, antibiotic, antifungal, astringent, antispasmodic, estrogenic, hypoglycemicand tonic agents. In the present investigation the specie, Salvia moorcroftiana was for the first time found infected with Sclerotium rolfsii Sacc. in Himachal Pradesh (India) causing typical crown rot symptoms, the losses of which amounted upto 25% in plantation areas surveyed during June-September 2011−12. Initially the symptoms appeared as yellowing and drooping of leaves proceeded by browning and later the leaves get distorted with wilting of plants and white cottony mycelial growth at the collar region. The mycelial growth spread to the stem and roots, with associated tissue rotting. The morphological characters of the crown rot causing fungus resembles to Sclerotium rolfsii. The botanicals and fungicides were considered for possible management of the disease. Out of eight plant leaf extracts, only three Melia azedarach, Bougainvellia and Aloe barbidensis showed high efficacy and recorded maximum inhibition of mycelial growth of the test pathogen (S. rolfsii) by 62.80, 58.61 and 55.34% over control under in vitro. Similarly fungicides, chlorothalonil, propineb, carbendazim and benlate not only reduced the disease incidence but improved the seed germination of the infected seeds and final plant stand with minimum pre- and post-emergence mortality rate hence can be recommended in managing the crown rot disease in Salvia moorcroftiana.